Keadilan dan Kepastian Hukum dalam Pemilu Serentak di Indonesia - Alfarizi, Aziz; Zwiki, Friz (Advances In Social Humanities Research, 2024)
The purpose of this study is to gain a deeper understanding of legal aspects, uphold the principles of electoral justice to realize a democratic (honest and fair) as well as a reference for education and research in strengthening legal and democratic life in the country. The research method applied in this article is a qualitative approach described through verbal reports to explain and describe the information that has been collected. Data sources in this study are divided into two types, namely primary data sources obtained directly from the field, and secondary data sources which are pre-existing information. The result of this study is that fairness in simultaneous elections in Indonesia has a significant impact on the integrity of the democratic process. Unfairness in elections, such as fraudulent practices, uneven distribution of resources, or impartiality in the administration of elections, can undermine the integrity of elections and reduce the representation of election results. When voters sense injustice, they may lose faith in the democratic system and doubt the legitimacy of the government that results from the election. To overcome the challenges of fairness in simultaneous elections in Indonesia, there needs to be a very strong commitment to strengthen the integrity and representativeness of the democratic process